'Dogged, Insightful, and Humane': Writing Women's Lives in Twenty-First-Century True Crime. (March 2022) - Friars, Rachel M.; Traynor, Jesyka
Abstract : Although studies have identified women as the primary audience of true crime, women's engagement with the genre is far from a passive one. Women producers of true crime participate in discussions of female victimhood, poverty, and law. They also consider the significance – and complexity – of writing women's lives within a genre like true crime. Our chapter analyses true crime texts by women to interrogate the changing focus of true crime in the twenty-first century and the labour that these authors participate in as they question established narratives of female victimhood. In our case studies of Hallie Rubenhold's The Five (2019) and Michelle McNamara's I'll Be Gone in the Dark (2018) we suggest that these texts model a feminist version of true crime by creating more comprehensive narratives of female victimhood and survival via narrative structures that centralise women's lives. We contend that these texts are engaged in crucial work that alters the language we use to speak about victims and victimhood.